2019
DOI: 10.1016/j.addbeh.2018.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Drug use patterns and associated factors among female sex workers in Iran

Abstract: Objective: This study examines the prevalence of drug and poly-drug use and their associated factors among female sex workers (FSW) in Iran. Methods: We analyzed data from a bio-behavioral surveillance survey of 1,347 FSW across 13 major cities in Iran in 2015. Two outcome measures were defined: i) past-month "any drug use", a binary variable defined as none or any; and ii) a three-category past-month "poly-drug use" variable defined as none, only one drug, and more than one drug. Correlates of these two study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…101,111,112,[114][115][116][117] Drug use has been commonly described, and has been associated with greater numbers of clients, forced sex and unstable housing. 118,119 Some cities have clinics dedicated to SW care; however, SWs who lack access to such clinics may face barriers to sexual health services due to lack of health insurance, mistrust of the healthcare system, local reliance on syndromic management and concern that positive tests may adversely affect their ability to work. Transgender and male SWs may also face intersectional compounded vulnerabilities based on transphobia and homophobia.…”
Section: Sex Workersmentioning
confidence: 99%
“…101,111,112,[114][115][116][117] Drug use has been commonly described, and has been associated with greater numbers of clients, forced sex and unstable housing. 118,119 Some cities have clinics dedicated to SW care; however, SWs who lack access to such clinics may face barriers to sexual health services due to lack of health insurance, mistrust of the healthcare system, local reliance on syndromic management and concern that positive tests may adversely affect their ability to work. Transgender and male SWs may also face intersectional compounded vulnerabilities based on transphobia and homophobia.…”
Section: Sex Workersmentioning
confidence: 99%
“…For example, Shokoohi et al [ 20 ] using national bio-behavioral surveillance survey data, showed that only 24.9% of facility-based FSWs reported past-month non-injection drug use. Moreover, lifetime injection drug use prevalence was reported as 6.1% in 2015 and 14.6% in 2010 national bio-behavioral surveillance surveys with facility-based participants [ 18 , 21 ]. The high prevalence of lifetime drug use among FSWs also reported among FSWs in Mazandaran (59.0%) [ 27 ] and shiraz (69.9%) [ 28 ] in the previous studies with small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…While our understanding about non-injection and injection drug use among FSWs is growing in Iran [ 20 ], less attention has been paid to the pattern of injection and non-injection drug use specifically among street-based FSWs. Studies with facility-based participants have estimated that that 24.9% and 14.6% of FSWs reported past-month non-injection drug use [ 21 ] and lifetime injection drug use [ 22 ]. Crystal methamphetamine use also has been reported by 15.0% of FSWs in Iran [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The survey procedures have been described in more detail elsewhere. 16,23 In brief, 1347 FSWs were recruited from 21 health centers and harm reduction sites in 13 major cities in Iran from January to August 2015. The majority of the participants (89%) were selected using non-probability facility-based sampling, while the rest were selected through outreach efforts from street-based venues.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…19,20 Although FSWs are still considered to be an understudied subpopulation in Iran, our understanding concerning the extent of risky behaviors among FSWs is growing. 17,[20][21][22][23][24] Meanwhile, less attention has been paid to the pattern of risky sexual practices and STIs among those FSWs with early sex work engagement such that they remain an under-recognized population in Iran and internationally. 1,25 Understanding the extent to which FSWs involve in early sex work and how they engage in high-risk behaviors are important for the development of prevention and harm reduction strategies.…”
Section: Introductionmentioning
confidence: 99%